2024
DOI: 10.1109/access.2024.3377688
|View full text |Cite
|
Sign up to set email alerts
|

Application of SCNGO-VMD-SVM in Identification of Gas Insulated Switchgear Partial Discharge

Wei Sun,
Hongzhong Ma,
Sihan Wang

Abstract: Partial discharge (PD) is one of the main reasons of insulation deterioration in gas insulated switchgear (GIS). How to efficiently and accurately identify PD signals is an important guarantee for the stable operation of GIS. In this paper, an improved northern goshawk optimization (SCNGO) is proposed, which automatically optimizes parameters of variational mode decomposition (VMD) and support vector machine (SVM) to realize fault identification of GIS PD. Firstly, to overcome the shortcomings that NGO is easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The resultant accuracy verified that IWOA had a good effect on the parameter optimization of SVMs. Sun et al also proposed an improved northern goshawk optimization (SCNGO) to optimize the parameter penalty factor and the kernel parameter of the SVM [7]. Fujioka et al utilized the maximum intensity observed in the PRPD pattern as the input data of an ANN [8].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant accuracy verified that IWOA had a good effect on the parameter optimization of SVMs. Sun et al also proposed an improved northern goshawk optimization (SCNGO) to optimize the parameter penalty factor and the kernel parameter of the SVM [7]. Fujioka et al utilized the maximum intensity observed in the PRPD pattern as the input data of an ANN [8].…”
Section: Introductionmentioning
confidence: 99%